Revisiting the phase diagram of LaFe1−xCoxAsO in single crystals by thermodynamic methods - Scaravaggi, Francesco; Sauerland, Sven; Wang, Liran; Kappenberger, R.; Lepucki, P.; Dioguardi, A. P.; Hong, X.; Caglieris, F.; Wuttke, C.; Hess, C.; Grafe, H.-J.; Aswartham, S.; et al. (Physical review, 2021)
In this work we revisit the phase diagram of Co-doped LaFeAsO using single crystals and thermodynamic methods. From magnetic susceptibility studies, we track the doping evolution of the antiferromagnetic phase to reveal a continuous suppression of TN up to 5% Co doping. To study the evolution of the so-called nematic phase, the temperature dependence of the length changes along the a and b orthorhombic directions, ΔL/L0, was determined by high-resolution capacitance dilatometry. The results clearly show a gradual reduction of the orthorhombic distortion δ and of TS with increasing Co content up to 4.5%, while it is completely suppressed for 7.5% Co. Bulk superconductivity was found in a small doping region around 6% Co content, while both Tc and the superconducting volume fraction rapidly drop in the neighboring doping regime. Ultimately, no microscopic coexistence between the superconducting and magnetic phases can be assessed within our resolution limit, in sharp contrast with other iron-pnictide families, e.g., electron- and hole-doped BaFe2As2.